The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.19044/ejes.v4no3a5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-Esteem, Academic Self-Efficacy and Perceived Stress on Academic Performance: A Cross-Sectional Study of Saudi Psychology Students

Abstract: Self-esteem, academic self-efficacy, perceived stress, and preferred learning styles have been linked to academic performance. Investigation of the relationships between these variables has mainly occurred with medical and dental tertiary students in Saudi Arabia, but no previous study has focused on psychology students. The main purpose of the current study was to assess stress levels and preferred learning styles, and examine the relationships between self-esteem, academic self-efficacy, perceived stress, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
(12 reference statements)
4
24
1
Order By: Relevance
“…Alyami et al (2017) conducted a study on 214 university students and revealed that academic self-efficacy has a positive and significant effect on their academic performance [28]. Other studies have shown that academic selfefficacy has a considerable effect on the students' learning, motivation, and academic performance [9,18,[29][30][31].…”
Section: The Effect Of Academic Self-efficacy On Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Alyami et al (2017) conducted a study on 214 university students and revealed that academic self-efficacy has a positive and significant effect on their academic performance [28]. Other studies have shown that academic selfefficacy has a considerable effect on the students' learning, motivation, and academic performance [9,18,[29][30][31].…”
Section: The Effect Of Academic Self-efficacy On Academic Performancementioning
confidence: 99%
“…According to the review of the literature, although many studies have been conducted on direct effect of variables as academic emotions, academic self-efficacy, metacognitive learning strategies and their roles in academic achievement, few studies have focused on direct and indirect relationship among these variables and investigated the role of emotions, self-efficacy, and metacognitive learning strategies together as predictors of academic achievement in a structural equation model. Previous studies have either investigated the effect of the above-mentioned variables on each other separately [2,36,42,48], or they have focused on fields other than medical education [1,4,10,28,32,46]. Therefore, according to the control-value theory [40], the expectancy-value theory of motivation [43], the social cognitive theory and review of the literature, the present study was designed to test the following research hypotheses and conceptual model (see Fig.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Alyami et al (2017) conducted a study on 214 university students and revealed that academic selfefficacy has a positive and significant effect on their academic performance (28). Other studies have shown that academic self-efficacy has a considerable effect on the students' learning, motivation, and academic performance (9,18,(29)(30)(31).…”
Section: The Effect Of Academic Self-efficacy On Academic Performancementioning
confidence: 99%
“…According to the review of the literature, although many studies have been conducted on direct effect of variables as academic emotions, academic selfefficacy, metacognitive learning strategies and their roles in academic achievement, few studies have focused on direct and indirect relationship among these variables and investigated the role of emotions, self-efficacy, and metacognitive learning strategies together as predictors of academic achievement in a structural equation model. Previous studies have either investigated the effect of the above-mentioned variables on each other separately (2,36,42,48), or they have focused on fields other than medical education (1,4,10,28,32,46). Therefore, according to the control-value theory (40), the expectancy-value theory of motivation (43), the social cognitive theory and review of the literature, the present study was designed to test the following research hypotheses and conceptual model (see Fig.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…The two authors also noted that it is difficult to identify with certainty a causal relationship between the two concepts, mainly due to the lack of a longitudinal research to prove it. Researchers studied the relationship between academic self-efficacy and academic self-concept [6] language learning motivation [7], academic performance and self-regulated learning [8], [9], [10], academic-related boredom [11], locus of control and self-concepts [12]. Perceived Academic Efficacy is a scale taken from PALS -The Patterns of Adaptive Learning Scales.…”
Section: Introductionmentioning
confidence: 99%